Housing industry development in Malaysia / Norzihan Molan - Molan, Norzihan (1988)
The study will emphasise on matters that cause the delay in getting the approvals, which normally take two to five years of processing time. 'Thus, the delay affects large sum of money which has to be borne by developers and builders.